A pragmatic and scalable strategy using mobile technology to promote sustained lifestyle changes to prevent type 2 diabetes in India—Outcome of screening. Issue 3 (December 2015) - Priscilla, Susairaj; Nanditha, Arun; Simon, Mary; Satheesh, Krishnamoorthy; Kumar, Sathish; Shetty, Ananth Samith; Snehalatha, Chamukuttan; Johnston, Desmond G.; Godsland, Ian F.; Wareham, Nicholas J.; Ramachandran, Ambady
Highlights: An effective, simple strategy for opportunistic screening of dysglycemia remains elusive. We used a two-step strategy, involving non-invasive risk assessment and estimation of glycated hemoglobin (HbA1c) for screening persons with high risk for diabetes for a primary prevention study of diabetes. Persons with HbA1c values between 6.0% (42.1 mmol/mol) and 6.4% (46.4 mmol/mol) were chosen for the study ( n = 1171). A total of 6030 non-diabetic persons were prescreened and 2835 underwent HbA1c assessment. The methodology used in assessment of lifestyle parameters and the use of SMS for education and motivation of the participants are described. Abstract: Aims: We describe a two-step screening approach using non-invasive risk assessment and glycated hemoglobin (HbA1c) to identify participants for a diabetes prevention trial. Methods: A total of 6030 non-diabetic persons of 35–55 years were screened using risk assessment for diabetes. Those with three or more risk factors were screened using point of care HbA1c test. For this study, participants in HbA1c categories of 6.0% (42.1 mmol/mol)–6.4% (46.4 mmol/mol) were selected and their characteristics were analyzed. Results: Among 6030 persons, 2835 (47%) had three or more risk factors for diabetes. Among those screened with HbA1c, 43.2% (1225) had HbA1c values of <6.0% (42.1 mmol/mol), 46.8% (1327) had HbA1c values between 6.0% (42.1 mmol/mol) and ≤6.4% (46.4 mmol/mol) and 10% (283) had undiagnosed diabetes with ≥6.5% (47.5 mmol/mol). Positive family history was present in 53.2%, 81.7% were obese and 14.8% were overweight. Conclusions: Opportunistic screening using a two-step approach: diabetes risk profile and HbA1c measurement detected a large percentage of individuals with prediabetes. Prediabetic persons recruited to the trial had higher percentage of obesity and presence of positive family history than those who had lower HbA1c values. Outcomes from this trial will enable comparisons with the previous prevention studies that used blood glucose levels as the screening criteria.